An Analysis of Anti-Fat Bias LibGuides: Are Libraries in the Thick of It? - Silkotch, Christie; Haines, Laura; Dolan, Amalia (Evidence Based Library and Information Practice, 2025)
Objective – This research investigates library research guides that share information about anti-fat bias to support weight-inclusive education or practice. By analyzing these guides, we seek to understand how academic librarians are engaging in this work and how they can continue to support weight inclusivity as educators, proponents of information literacy, and interdisciplinary partners.Methods – The authors searched for and screened publicly available LibGuides from academic libraries that included content about anti-fat bias, weight stigma, and/or body liberation. Relevant guides were then evaluated with an original framework to examine their content for insight about their target audience and context.Results – The authors identified and analyzed 36 relevant LibGuides, predominantly from college and university libraries. Thirty-three LibGuides came from institutions in the United States, and most of the institutions had at least one health sciences program, though eight offered no health-related programs. Thirty-two of the analyzed LibGuides presented anti-fat bias content in a tab within a larger guide, while the remaining few were standalone guides. The majority of guides with tab-level anti-fat bias content presented it as a social justice issue, though a few framed the content in a nutrition or other context. The most popular resource types offered in the guides were books, popular articles, videos, associations/organizations, and academic articles.Conclusion – Weight inclusivity discourse is growing across disciplines and is an area that librarians are well-situated to support. Presenting anti-fat bias as a social justice and diversity, equity, inclusion, and accessibility (DEIA) issue in libraries is promising and highlights library workers’ commitment to anti-oppression efforts and learning. Work remains to be done to integrate more anti-fat bias content into academic curricula and education, and librarians should look to engage with disciplinary educators, learners, and colleagues to grow and support this work, particularly in the context of the health sciences.